On the retrieval of significant wave heights from spaceborne Synthetic Aperture Radar (ERS-SAR) using the Max-Planck Institut (MPI) algorithm - Nelson Violante-Carvalho (Anais da Academia Brasileira de Ciências, 2005)
Synthetic Aperture Radar (SAR) onboard satellites is the only source of directional wave spectra with continuousand global coverage. Millions of SAR Wave Mode (SWM) imagettes have been acquired since thelaunch in the early 1990s of the first European Remote Sensing Satellite ERS-1 and its successors ERS-2and ENVISAT, which has opened up many possibilities specially for wave data assimilation purposes. Themain aim of data assimilation is to improve the forecasting introducing available observations into the modelingprocedures in order to minimize the differences between model estimates and measurements. Howeverthere are limitations in the retrieval of the directional spectrum from SAR images due to nonlinearities inthe mapping mechanism. The Max-Planck Institut (MPI) scheme, the first proposed and most widely usedalgorithm to retrieve directional wave spectra from SAR images, is employed to compare significant waveheights retrieved from ERS-1 SAR against buoy measurements and against the WAM wave model. It isshown that for periods shorter than 12 seconds theWAMmodel performs better than the MPI, despite the factthat the model is used asfirst guess to the MPI method, that is the retrieval is deteriorating thefirst guess. Forperiods longer than 12 seconds, the part of the spectrum that is directly measured by SAR, the performanceof the MPI scheme is at least as good as the WAM model.